Consultation rates among middle aged men in general practice over three years. Issue 6753 (29th September 1990) - Cook, D G; Morris, J K; Walker, M; Shaper, A G
Abstract : OBJECTIVE–To provide data on consultation rates in general practice for middle aged men over three years according to their age and social class. DESIGN–Prospective study of men over eight years. Data on consultation rates during years 6-8 were collected retrospectively from practice records. SETTING–Over 1000 general practices in Great Britain by year 8. Initially (in 1978-80) the men had been selected at random from one practice in each of 24 towns. SUBJECTS–7013 Men aged 46-65 in the sixth year of follow up. MAIN OUTCOME MEASURE–Number of consultations a year over three years. RESULTS–The mean annual consultation rate over the three years rose steadily with age (7.0 at age 46-50 to 9.7 at age 61-65) and with social class (6.4 in class I to 10.0 in class V) but was potentially misleading as the distribution was skew: 10.5% of men (736) did not consult over the three years and 17.2% (1209) consulted only once or twice, whereas 11.4% (798) of men were seen more than 18 times. The percentage of men who did not consult over three years fell only slightly with age and was unrelated to social class, with roughly a tenth of all age and social class groups not consulting. Two thirds of non-consulters in year 6 (1598/2334) consulted in year 7 or 8. CONCLUSIONS–The mean is not an appropriate summary measure of consultation rates and may conceal important differences among practices or other groups. The new general practitioner contract stipulates that all patients aged 16-74 must be provided with information to promote health and prevent illness at least once every three years. Most practices will have to approach a tenth of their men aged 46-65 specially to provide this service even if one consultation in three years is regarded as sufficient to allow a service to be provided.